Chronic daily headache: literature review on management and prevention - Scabeni, Bruna Verdi; Araújo, Andrina Pereira De; Silva, Eloisa Gonçalves Da; Mascarello, Júlia; Costa, Karine Vitória Viana Da; Silva, Marcela Guedes Ferreira Da; Oliveira, Millena Silva De; Nascimento, Nicole Reis (Headache Medicine, 2024)
Introduction: Chronic daily headache (CDH) has a multifactorial etiology and is defined as a migraine lasting more than 4 hours per day for 15 or more days per month. It can be subdivided into three modalities: chronic tension-type headache, new daily persistent headache, transformed migraine, and hemicrania continua. Its high prevalence is a significant public health issue, given the substantial impact on individuals' quality of life and the high cost to public and private sectors.Objective: To understand the management and prevention of chronic daily headache.Methods: This research is a narrative literature review, with scientific articles sourced from Google Scholar, LILACS, PubMed, and BVS databases. The descriptors used were "chronic daily headache," "management," and "prevention." Inclusion criteria were (a) articles available in English and Portuguese and (b) articles available for free. Exclusion criteria were (a) articles that do not fit the theme and (b) not available for free.Results: Patients with CDH often manifest psychological symptoms and psychosomatic manifestations, usually presenting a significant family history of headaches. The quality of pain is variable, ranging from pressure-like to tightness, and may also include stiffness or tension in the neck muscles. Regarding pain location, the most common topographies are bifrontal, occipitonuchal, bitemporal, vertex, and holocranial. The primary management approach is prophylactic medication treatment, where the choice of the agent should be based on the type of CDH, side effects, and comorbidities presented. Examples of medications include antidepressants, antiepileptics, antihypertensives, and anti-serotonergic drugs. Another measure is the implementation of non-pharmacological therapies, such as cognitive-behavioral therapies and healthy lifestyle habits, with special attention to sleep.Conclusion: Chronic daily headache is a challenge for medical care in terms of its management and prevention, given the variety of diagnostic alternatives and the diversity of disorders that contribute to the development of this condition. Thus, it is evident that CDH is a generalist term and "diagnosis," making it necessary for the neurologist to perform differential evaluations to determine the type of headache and its appropriate treatment.